2019
DOI: 10.1080/23320885.2018.1564314
|View full text |Cite
|
Sign up to set email alerts
|

Intertendinous epidermoid cyst of the forearm

Abstract: As epidermoid cysts generally originate from hair follicle infundibulum, they appear as intradermal or subcutaneous tumors and are very rare in locations away from the skin. Here, we report a rare case of intertendinous epidermoid cyst of the forearm in a 68-year-old man that was treated surgically. ARTICLE HISTORY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A literature review showed purely intramuscular epidermoid cysts, though rare, that have previously been described in the erector spinae, 1 forearm, 2 and gluteal muscles. 4 We found no instance prior to this of an epidermoid cyst in the temporalis muscle.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A literature review showed purely intramuscular epidermoid cysts, though rare, that have previously been described in the erector spinae, 1 forearm, 2 and gluteal muscles. 4 We found no instance prior to this of an epidermoid cyst in the temporalis muscle.…”
Section: Discussionmentioning
confidence: 90%
“… 1 The two hypotheses for their origin include either epidermal cells driven inwards by trauma in the distant past or following aberrant implantation of ectoderm during embryogenesis. 1 2 They enlarge due to slow accumulation of secretions inside them, and the term giant epidermoid cyst is used when the size of the lesion is greater than 5 cm in size. 3 …”
Section: Discussionmentioning
confidence: 99%
“…[33] The etiology of acquired epidermoid cysts may result from the ectopic transfer of epithelial cells into the deeper tissues of the skin by friction, trauma, surgery, and so on, which gradually proliferate and keratinize. [34][35][36] Multiple epidermoid cysts are currently studied mostly in relation to genetic history, which can occur in Gardner syndrome caused by a colon gene mutation in adenomatous polyposis, [37] or in Lowe syndrome of X chromosome eye-brain-kidney disease caused by OCLR1 gene mutation. But the exact pattern of mutations has not been elucidated in current studies and needs to be further investigated.…”
Section: Etiologymentioning
confidence: 99%
“…Intramuscular epidermal cysts are a rarity 1 and when reported usually extend inward from their usual origin in the layers of the skin. There are very few instances of purely intramuscular epidermal cysts where no connection with the surface could be documented, 2 3 4 and in such cases, the origin is speculated to be either from embedded epidermal elements driven in by trauma 2 or from implantation of ectodermal cells during embryogenesis. 4 In our case, the lesions were bilateral and fairly symmetric, and since there was no history of trauma, we speculate that they may have developed from anomalous cell nests that were sequestrated in the muscle during embryological development.…”
Section: Figmentioning
confidence: 99%
“…Mere absence of continuity with the skin cannot exclude the diagnosis, as these lesions can occur at any site and at any depth from the surface. 4 Differential diagnosis includes intramuscular lipomas (which will be T1-hyperintense on MRI and completely hypodense on CT scans), intramuscular hematomas (will have surrounding muscle contusion while old lesions may have calcification on CT scans), fibromas and soft-tissue sarcomas (will not be well-demarcated on imaging), and vascular malformations like hemangiomas (will show flow on doppler USG). The characteristic MRI and CT imaging features of a well-demarcated lesion with no muscle involvement and twinkling artifact on Doppler USG (due to the keratinaceous semisolid debris of the cyst 5 ) can clinch the diagnosis.…”
Section: Figmentioning
confidence: 99%